Diet Serbuk Kunyit (Curcuma longa L.) sebelum Pubertas Terhadap Performa Ayam Kampung (Gallus gallus domesticus) - Sukarman Hadi Jaya Putra (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study was to analyze the effectiveness of turmeric powder diet as a supplement on the performance of native chickens. The diet is given before entering puberty, so that it can have an optimal impact on the physiology of the reproductive organs of native chickens. The research design used was a completely randomized design (CRD) with 3 treatments, namely a dose of turmeric powder given to standard feed. The doses used were 0 mg/chicken/day, 216 mg/chicken/day and 324 mg/chicken/day. Each treatment consisted of 5 replications. Therefore, 15 test cages are needed. Each test drum was filled with 3 female free-range chickens that had not yet entered puberty. The age of the free-range chicken used was 4 months. The period of giving turmeric powder treatment is 60 days. Data on weight and egg laying rate were measured for 2 months of observation. Data was observed every day, and accumulated every 28 days. All measurement data were analyzed by analysis of variance (ANOVA). The data that has been analyzed explains that native chickens given turmeric powder supplements have a higher production rate in each month of observation compared to chickens that are not given turmeric powder diet before puberty. The administration of turmeric powder with the highest dose of 324 mg/chicken/day succeeded in increasing the weight of free-range chicken eggs each month of observation, respectively in the 1st month as much as 866.2 g and the 2nd month as much as 996.8 g. Therefore, turmeric powder diet has a positive impact on the performance of native chickens every month of observation.